Utilização de métodos combinados de avaliação imobiliária para a elaboração da planta de valores genéricos - Dalaqua, Roberto Ruano [UNESP]; Amorim, Amilton [UNESP]; Flores, Edilson F. [UNESP] (My University, 2010)
The Plant of Generic Values (PVG) is part of the cadastral system of a city hall and is about an important document or support for the urban planning. For its conception some stages are necessary, amongst which the most remarkable: the collection of information and the proper evaluation. A norm number 14653-2 of the ABNT recommends the application of the comparative method of data of market for the evaluation of lands values, but not always this procedure is possible due to absence of significant samples, as in urban areas densely constructed the real estate transactions is restricted, practically, to remarkable are the constructed ones. Thus, this work aims at showing which one, the sources of these data and the problematic found to get them. Moreover, a method is presented, that is an alternative to get the values of lands in the regions where yhere is scarcity of these data, so as to make the results beter. This method deals with the junction of other methods of evaluation to the comparative method of market data. The use of the methodology provided better performance in the procedures, having as a consequence bigger uniformity between the data, that is, the value of evaluation and the value of market equalize. Besides, the separation of the area of work in zones of homogeneous data made possible to generate more models, making use of fewes variables, due to the similarity among the data.
The use of combined methods of market data for the evaluation of the plant of generic values
Keywords: Cartography; Multivariate analysis; PVG; Real estate evaluation